1993
DOI: 10.1016/0304-3959(93)90190-z
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of multidimensional clinical outcome in chronic low back pain patients

Abstract: Individuals with persisting pain often present a constellation of symptoms that includes pain, health-related impairment and dysphoric mood. It is now widely accepted that comprehensive assessment must address each of these dimensions. Despite recognition of the value of multidimensional assessment, no empirical efforts have validated the construct of a multidimensional clinical outcome presentation based on the dimensions of pain, impairment and dysphoric mood. We employed cluster analytic procedures on stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
44
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 41 publications
12
44
1
1
Order By: Relevance
“…14,36,66,74 Both clusters have been repeatedly identified in the literature among patients with chronic pain and also among patients with more specific etiology such as low back pain, spinal pain, temporomandibular joint disorders, and headache. 5,46,64,76 Rudy et al 64 identified a dysfunctional profile (42.6%, all high) and a minimizer/ adaptive coper profile (29.5%, all low), similar to our findings. When tested, their clusters were not related to gender, age, pain duration, or number of medical conditions by using the IASP classification.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…14,36,66,74 Both clusters have been repeatedly identified in the literature among patients with chronic pain and also among patients with more specific etiology such as low back pain, spinal pain, temporomandibular joint disorders, and headache. 5,46,64,76 Rudy et al 64 identified a dysfunctional profile (42.6%, all high) and a minimizer/ adaptive coper profile (29.5%, all low), similar to our findings. When tested, their clusters were not related to gender, age, pain duration, or number of medical conditions by using the IASP classification.…”
Section: Discussionsupporting
confidence: 94%
“…Klapow et al used similar dimensions to classify their study sample and identified a group of patients with high pain, low depression, and low pain impact. 46 The differences between our results and theirs might be related to the measures (MPQ, Sickness Impact Profile, and BDI) and the sample used (men with chronic low back pain without any major comorbidities). Our study used a mixed pain model, an ethnically diverse population, and included both men and women who had comorbid conditions.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations